Language Learning Difficulties Reported by Beginner-Level Learners of Arabic Using Online Tools - Amer, Mahmoud (JOURNAL OF ADVANCES IN LINGUISTICS, 2020)
This study examined how two classes used online supplementary material to learn Arabic and the difficulties they reported in the process of their learning. The two classes have a total of 33 students who completed the course. The data from their weekly journal entries and log information from the site where the material was housed are used to describe the extent and the ways in which students used the material and issues they faced learning Arabic. Results show that students in both classes spent roughly 265 hours practicing Arabic with an average of 8 hours per student throughout the semester and that vocabulary recall and pronunciation were key struggles in their learning. Furthermore, this paper discusses some of the themes that emerged of students’ journal entries about their learning Arabic. Further implications are provided and discussed.